FRI0013 Acpa-induced mobility of primed synovial fibroblasts: the missing link between acpa-induced bone loss and synovial changes. (15th June 2017) - Sun, M; Joshua, V; Krishnamurthy, A; Hensvold, AH; Liu, Y; Catrina, SB; Ospelt, C; Malmström, V; Steen, J; Engström, M; Wähämaa, H; Rethi, B; et al.
Abstract : Background: Anti-citrullinated proteins antibodies (ACPAs) injected in mice induce IL-8 dependent bone loss and arthralgia, but no synovial changes. We hypothesized that additional stimulus, sensitizing the synovial compartment to ACPA effects, is needed for the transition from bone to synovial pathology. Methods: Synovial fibroblasts (SFs) were isolated from synovial tissue of RA patients by enzymatic digestion. Polyclonal ACPA and other non-ACPA IgGs were separated from peripheral blood of RA patients by affinity purification on a cyclic citrullinated peptide (CCP)-2 column. SF migration capacity was tested by scratch-assays in starved and non-starved cultures treated with ACPAs, with or without presence of IL-8. The results were evaluated by NIH ImageJ software. SF adhesion was analyzed by xCELLigence System Real-Time Cell Analyzer (ACEA bioscience). Peptidylarginine deiminases (PAD) expression and protein citrullination were evaluated by immunohistochemistry. The role of signaling pathways in the ACPA-mediated SF modulation was analyzed by using specific signal inhibitors and by monitoring protein phosphorylations using western blot. Results: Serum starvation of SF increased citrullinated proteins and PAD expression. Starved but not non-starved SF showed an increased mobility index following polyclonal ACPA stimulation to a mean±SD fold increase of 2.6±0.5. This effect was abolished by PAD inhibition as well as ACPA blocking with citrullinated but not native fibrinogen. Exogenous pro-inflamamatory cytokines (IL-8 and TNF) synergistically increased SF mobility when added together with ACPA. Phosphorylation and inhibition studies of intracellular signalling pathways in starved SF indicated an important role for PI3K-mediated signals in the ACPA-induced increase of SF mobility. Conclusions: We demonstrated that additional stimuli (such as stress-induced citrullination and cytokine priming) were needed for SF to react upon ACPA stimulation. This is an indirect proof supporting the idea that a synovial insult that will normally resolve unobserved, might be essential for the transition towards chronic synovial changes in the presence of ACPA. Disclosure of Interest: None declared